A box model to represent estuarine dynamics in mesoscale resolution ocean models. (April 2020) - Verri, Giorgia; Pinardi, Nadia; Bryan, Frank; Tseng, Yu-heng; Coppini, Giovanni; Clementi, Emanuela
Abstract: Representing the net freshwater flux at river mouths is challenging for global and regional scale ocean modelling. Although rivers are well known to affect both the coastal and basin-wide circulation and dynamics, coarse resolution ocean models cannot resolve the estuarine dynamics and are usually forced at river outlets in a simplistic way, with climatological runoff and zero or constant salinity values. The aim of this study is to provide a more realistic representation of the estuarine water inputs to a coarse but eddy-resolving regional model. First, the river volume transport and salinity values at the outlets are modelled with three different Estuary Box Models (EBMs) for stratified estuaries: the Knudsen relations model, a published EBM, called UCONN-NCAR EBM, which parameterizes the tidal inflow and mixing inside the estuary, and a new model, called CMCC-EBM. The CMCC EBM has been conceived to represent the estuarine processes coupled to a mesoscale resolving hydrodynamic model that resolves the entering flow field at the estuary mouth and it offers a new representation of the tidal inflow and a new salinity tidal mixing parameterization via horizontal diffusive processes. The Ofanto and Po rivers flowing into the Adriatic Sea (northern part of the central Mediterranean Sea) are selected as case studies. The coupling of the eddy resolving ocean model to the CMCC EBM is found to outperform the one with the UCONN-NCAR EBM in the region of freshwater influence on the shelf areas. Highlights: Riverine release affects both coastal and open sea circulation and dynamics. Regional and global mesoscale ocean models cannot resolve the estuarine dynamics. A wide implementation of estuary box models has started. Tidally averaged two-layer flow is a reasonable representation for stratified estuaries. The proposed EBM gives realistic estimates of river release and buoyancy plume.